PERSEPSI MASYARAKAT DESA NUSAPATI TERHADAP KEBERADAAN HUTAN MANGROVE KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Diniansyah, Jhony Sastro; Lumangkun, Augustine; Wardenaar, Evi (JURNAL HUTAN LESTARI, 2017)
The purpose of this research is to know the local people’s perception toward the existence of mangrove forest and to know the relationship from the factor of age, knowledge, cosmopolitan and income with the people’s perception of mangrove forest in Sungai Pinyuh Subdistrict, Mempawah District. This research used a survey method with interview technique. The respondents were sampled by purposive sampling. The number of sample was a hundred respondents. The respondensts were taken from three subvillage that are Subvillage I, Subvillage II, and Subvillage III. The data were analyzed by associative descriptively and using chi kuadrad. The results of this research are : The existence of mangrove forest, with the value count = 57,25 > 0,05 = 5,591 shows that there is a high relationship the existence of mangrove forests. The age level with the value count = 2,98 < 0,05 = 9,488 shows that it is unacceptable or there is no relatiaonship the existence of mangrove forests. The knowledge level with the value count = 14,60 > 0,05 = 9,488, shows that it is acceptable or there is a relationship the existence of mangrove forests. For the cosmopolite level with the value count = 3,04 < 0,05 = 9,488, shows that it is unacceptable or there is no relationship the existence of mangrove forests. and the income know level with the value count = 3,93 < 0,05 = 9,488 shows that it is unacceptable or there is no relationship the existence of mangrove forests. Keywords: Mangrove Forest, Perception, Relationship